Atraumatic restorative treatment in permanent teeth: an integrative literature review (Research, Society and Development, 2022)
Introduction: Minimal Intervention Dentistry (MI) is a treatment philosophy that considers the management of carious lesions with conservative techniques. Among them the Atraumatic Restorative Treatment (ART). This research sought to review the literature on the longevity of ART with high viscosity glass ionomer cement. Methodology: This is an integrative literature review study in which data were collected from primary studies, through qualitative systematic analysis, following the PRISMA parameters. From the guiding question: “What is the longevity of atraumatic restorations in permanent teeth?” through the PICO criteria, using the PubMed database. Results: Collection of articles, data extraction. Twelve articles were selected between the years 2005 and 2020 that fit the theme. Countries like Brazil and China were the most participatory. Favorable results were found regarding the use of the ART technique, in which the CIVAV presented results comparable to CR and superior to conventional VSDs in a follow-up period of 1-5 years. The brands most used in the studies were Maxion, Fuji II, Vitremer and Filtek. One of the main causes of failure was material loss/wear. Conclusion: it was possible to conclude that despite the heterogeneity (in terms of the best technique and best material to be used), ART has good results compared to the conventional technique, with no significant differences, and CIVAV is equal in survival and success to CR. However, replacing them with conventional IVCs does not guarantee the same results.